Jianpiyifei II Granules Suppress Apoptosis of Bronchial Epithelial Cells in Chronic Obstructive Pulmonary Disease via Inhibition of the Reactive Oxygen Species-Endoplasmic Reticulum Stress-Ca2+ Signaling Pathway - Fan, Long; Li, Leng; Yu, Xuhua; Liang, Ziyao; Cai, Tiantian; Chen, Yuanbin; Xu, Yinji; Hu, Tao; Wu, Lei; Lin, Lin (Frontiers in Pharmacology, 2020)
Jianpiyifei II granules (JPYF II), a herbal formula, are used for the treatment of chronic obstructive pulmonary disease (COPD) in Guangdong Provincial Hospital of Chinese Medicine. The protective effects of JPYF II against bronchial epithelial cell apoptosis in mice exposed to cigarette smoke (CS) and apoptosis of human bronchial epithelial cell lines (BEAS-2B and 16-HBE) stimulated with cigarette smoke extract (CSE) were investigated. Mice were exposed to CS generated from 4 cigarettes/day for 30 days and administered a dose of JPYF II (0.75, 1.5 and 3 g/kg/d) from the third week of CS exposure. In mice exposed to CS, JPYF II significantly inhibited CS-induced apoptosis and overexpression of endoplasmic reticulum (ER) stress-related markers in bronchial epithelial cells of the lung tissues. In CSE-stimulated BEAS-2B and 16-HBE cells, JPYF II attenuated apoptosis and cell cycle arrest in the G0/G1 phase. Mechanistically, CSE initially induced intracellular reactive oxygen species (ROS) production, which then triggered ER stress, leading to the release of Ca2+ from ER inositol trisphosphate receptor (IP3R)-mediated stores and finally cell death. Treatment with JPYF II resulted in a significant reduction in CSE-induced apoptosis through interruption of the ROS-ER stress-Ca2+ signaling pathway. Therefore, the results of this study have revealed the underlying mechanism of action of JPYF II in the treatment of COPD.